Correlates of Suicidal Behaviours among University Students in Nigeria - Ebohon, V. S.; Osagiobare, O. E. (NIU Journal of Social Sciences; Vol 9 No 3 (2023): NIU Journal of Social Sciences, Vol. 9 No. 3, September 2023DO - 10.58709/niujss.v9i3.1719, 2023)
The study examined the correlates of suicide and suicidal behaviours among university students in Edo State. Four research questions and two null hypotheses tested at 0.05 level of significance guided the study.  The descriptive explanatory mixed research design which respectively involves quantitative and qualitative phases was adopted for the study. The sample of 720 students were drawn from the population of 79,813 using the multi-stage sampling procedure. Three research instruments were used to obtain data used for the study. The self-designed questionnaire and interview schedule items were validated by three experts from Faculty of Education, University of Benin. The reliability of the instrument was established through a Cronbach’s Alpha statistics. Thus, Cronbach’s Alpha values of .81 and .68 were respectively obtained as the reliability values of the instrument (questionnaire). However, the checklist and the interview schedule theme and items were not subjected to reliability test. Data were analyzed using percentage, Chi- Square and Multiple Regression statistics. The findings revealed that substance abuse was the most prevalent suicidal behaviour among university students; there was a low level of suicide attempts among university students. However, there was a significant influence of family type, and permissive parenting style (the strongest predictor) on the causes of suicide and suicidal behaviour among university students in Edo State. It was concluded that suicide and suicidal behaviours among university students in Edo State is predicated on poor relationship with family members. It was therefore recommended among others that parent should be more responsible, bearing in mind that parenting is beyond providing food, money, shelter, clothing and other needed school materials as such parents should show more cares and apt attention to their children Keyword: Family Types, Parenting Styles, Suicide, Suicidal Behaviours, University Students